2013
DOI: 10.1016/j.ydbio.2013.06.028
|View full text |Cite
|
Sign up to set email alerts
|

Maldevelopment of dermal lymphatics in Wnt5a-knockout-mice

Abstract: Maintenance of tissue homeostasis and immune surveillance are important functions of the lymphatic vascular system. Lymphatic vessels are lined by lymphatic endothelial cells (LECs). By gene micro-array expression studies we recently compared human lymphangioma-derived LECs with umbilical vein endothelial cells (HUVECs). Here, we followed up on these studies. Besides well-known LEC markers, we observed regulation of molecules involved in immune regulation, acetylcholine degradation and platelet regulation. Mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 55 publications
0
36
0
5
Order By: Relevance
“…In the case that the Pmm2 morpholino was co-injected with wnt5a, a significant loss of papc expression was detected (ror2-wnt5a +Pmm2 Mo). As negative controls, uninjected and ror2 injected caps were analysed, showing background papc signals length, as well as shortening of the mandible, head, limbs and tail (Buttler et al 2013). Furthermore mutations in the wnt5a and ror2 gene lead to the Robinow syndrome in man, which is characterized foremost by short stature and abnormalities of the head and facial area (Person et al 2010;Brunetti-Pierri et al 2008;Bokhoven et al 2000), also resembling symptoms found in the Xenopus Pmm2 morphants.…”
Section: Discussionmentioning
confidence: 99%
“…In the case that the Pmm2 morpholino was co-injected with wnt5a, a significant loss of papc expression was detected (ror2-wnt5a +Pmm2 Mo). As negative controls, uninjected and ror2 injected caps were analysed, showing background papc signals length, as well as shortening of the mandible, head, limbs and tail (Buttler et al 2013). Furthermore mutations in the wnt5a and ror2 gene lead to the Robinow syndrome in man, which is characterized foremost by short stature and abnormalities of the head and facial area (Person et al 2010;Brunetti-Pierri et al 2008;Bokhoven et al 2000), also resembling symptoms found in the Xenopus Pmm2 morphants.…”
Section: Discussionmentioning
confidence: 99%
“…Wnt5a is also involved in lymphatic formation in the mouse, although at later developmental stages. Specifically, Wnt5a KO mice display defects in dermal lymphatic sprouting, which were primarily attributed to activation of the non-canonical pathway (Buttler et al, 2013).…”
Section: Transcriptional Control Of Lymphatic Cell Fate Specificationmentioning
confidence: 99%
“…This discrepancy is not surprising since Wnt signaling often presents distinct outcomes depending on cell or tissue type and developmental versus pathological stage [11]. Recently, a study on Wnt5a conventional (non-conditional) knockout mice showed reduced number but increased size of dermal lymphatic capillaries at embryonic day 18.5 [12], which indicates a developmental defect resulting from cumulative role of Wnt5a in all cell types, known and yet-to-be determined. In contrast, we observed reduced number but not increased size of lymphatic vessels in this inflammation study on adult mice taking advantage of the cell type-specific conditional knockout mice.…”
mentioning
confidence: 99%